BENCHMARKING THE TRAVEL AND TOURISM COMPETITIVENESS OF UZBEKISTAN AGAINST REGIONAL PEERS: A PILLAR-LEVEL GAP ANALYSIS WITHIN THE TTDI FRAMEWORK - B. Sobirov (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This study benchmarks the travel and tourism competitiveness of Uzbekistan against twelve comparator economies, including its immediate Caucasus and Central Asian (CCA) peers and three global tourism leaders, using a seventeen-pillar adaptation of the Travel and Tourism Development Index (TTDI). Method: A composite-index and gap-decomposition methodology is applied: pillar scores are aggregated into five thematic sub-indices, a competitiveness gap vector is computed against the peer mean, and the competitiveness-arrivals relationship is tested through bivariate regression. Results: Uzbekistan records an overall score of 3.68, ranking eleventh in the sample and 0.18 points below the unweighted comparator mean. The decomposition reveals a sharply bifurcated profile: the country is competitive on safety and security (6.17), price (5.49) and demand sustainability (4.13), but lags substantially on tourist-services infrastructure (1.45), cultural resources (1.85) and travel-and-tourism prioritization (3.30). A statistically meaningful positive association is found between competitiveness and arrivals across the sample. The findings indicate that Uzbekistan's competitiveness deficit is concentrated in policy-amenable infrastructure and resource-valorization pillars rather than in structural endowments, and a prioritized intervention sequence is proposed. Novelty: This study benchmarks the travel and tourism competitiveness of Uzbekistan against twelve comparator economies, including its immediate Caucasus and Central Asian (CCA) peers and three global tourism leaders, using a seventeen-pillar adaptation of the Travel and Tourism Development Index (TTDI). A composite-index and gap-decomposition methodology is applied: pillar scores are aggregated into five thematic sub-indices, a competitiveness gap vector is computed against the peer mean, and the competitiveness-arrivals relationship is tested through bivariate regression.